The Ras Mutant D119N Is Both Dominant Negative and Activated - Cool, Robbert H. (American Society for Microbiology, 1999)
The introduction of mutation D119N (or its homolog) in the NKxD nucleotide binding motif of various Ras-like proteins produces constitutively activated or dominant-negative effects, depending on the system and assay. Here we show that Ras(D119N) has an inhibitory effect at a cell-specific concentration in PC12 and NIH 3T3 cells. Biochemical data strongly suggest that the predominant effect of mutation D119N in Ras—a strong decrease in nucleotide affinity—enables this mutant (i) to sequester its guanine nucleotide exchange factor, as well as (ii) to rapidly bind GTP, independent of the regulatory action of the exchange factor. Since mutation D119N does not affect the interaction between Ras and effector molecules, the latter effect causes Ras(D119N) to act as an activated Ras protein at concentrations higher than that of the exchange factor. In comparison, Ras(S17N), which also shows a strongly decreased nucleotide affinity, does not bind to effector molecules. These results point to two important prerequisites of dominant-negative Ras mutants: an increased relative affinity of the mutated Ras for the exchange factor over that for the nucleotide and an inability to interact with the effector or effectors. Remarkably, the introduction of a second, partial-loss-of-function, mutation turns Ras(D119N) into a strong dominant-negative mutant even at high concentrations, as demonstrated by the inhibitory effects of Ras(E37G/D119N) on nerve growth factor-mediated neurite outgrowth in PC12 cells and Ras(T35S/D119N) on fetal calf serum-mediated DNA synthesis in NIH 3T3 cells. Interpretations of these results are discussed.